2010
DOI: 10.3109/09638237.2010.492415
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to acute mental health services in a general hospital

Abstract: The UCC model of care contributed to improved access to psychiatric evaluation and short-term treatment. This inter-professional model could be applied to other health care settings to meet the needs of patients requiring acute psychiatric services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The rationale for a multidisciplinary approach was rarely explicitly stated; however, it may be intended to expand the volume of patients who could be seen (for example, through joint assessment, either in a single appointment or asynchronously) and (or) to expand the comprehensiveness of services (for example, psychotherapies). 10,22,23 Few programs specifically described how providers of different disciplines interfaced in the care of patients. Thus it is unclear whether care was truly interprofessional and teambased (as opposed to multidisciplinary), how roles were defined and negotiated, how communication occurred, and how clinical deterioration and (or) risks were handled.…”
Section: Staffingmentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale for a multidisciplinary approach was rarely explicitly stated; however, it may be intended to expand the volume of patients who could be seen (for example, through joint assessment, either in a single appointment or asynchronously) and (or) to expand the comprehensiveness of services (for example, psychotherapies). 10,22,23 Few programs specifically described how providers of different disciplines interfaced in the care of patients. Thus it is unclear whether care was truly interprofessional and teambased (as opposed to multidisciplinary), how roles were defined and negotiated, how communication occurred, and how clinical deterioration and (or) risks were handled.…”
Section: Staffingmentioning
confidence: 99%
“…Overall, programs reported improvements in clinical outcomes, including clinician-assessed mental health and psychosocial functioning 10 and various patient-reported clinical outcomes, including: improvements in levels of distress, 22,27 self-efficacy, 27 mental health symptom severity, 10 and mental health-related quality of life and subjective well-being. 10 However, in the RCT of the Rapid Response Outpatient Team, Greenfield et al 17 reported no between-group differences in overall functioning (measured by the Children's Global Assessment Scale) or levels of suicidality (measured by the Spectrum of Suicidal Behavior Scale) for the intervention group (n = 158), compared with the usual care group (n = 128), at 6-month follow-up.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…This rise in number of referrals to psychiatric emergency services has led many medical centers to develop crisis intervention facilities aimed at delivering emergency psychological and medical care to patients suffering from acute distress. These crisis intervention units offer immediate and proximal interventions delivered by an interdisciplinary team of well-trained professionals in the fields of psychiatry, psychology, social work, and psychiatric nursing (Kowal et al, 2011). Although the settings, treatment approaches, and durations of intervention vary from one unit to another, most of the crisis intervention units also deliver short-term, intensive, and crisis-focused psychotherapy (see Sunderji et al, 2015 for review).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies assessing crisis intervention have focused on the outcomes of these interventions, and in general showed a favorable outcome. For example, Kowal et al (2011) evaluated the effectiveness of an urgent consultation clinic (UCC) and found significant improvements in life satisfaction, overall functioning, and mental quality of life. Wand et al (2012) evaluated an emergency-department-based mental health outpatient service and found decreases in patients’ levels of distress.…”
Section: Introductionmentioning
confidence: 99%